Happiness at Workplace - Fitria Rahmi (Fakultas Ilmu Pendidikan)
Entering the 21st century, the company no longer focuses on the expertise that employees have, but rather on optimizing the quality and function, as well as the positive work experience that employees have. This current situation shows that happiness is one of the important issues that need to be considered especially in the world environment. Happiness in the work place refers to employee satisfaction with their works and lives (Wesarat, Sharif & Majid, 2015).Employees who feel the happiness at work tend to focus more on their work and increase their productivities. Happiness at work is influenced by job satisfaction, job engagement, workplace security, managing stress and self-confidence. Furthermore, this paper will have a review of definitions, factors that influence happiness, the importance of happiness in the workplace and exposure to some of the results of previous research both outside and in Indonesia so that it can be an input for further research, remembering happiness is an important domain especially in life in the work environment.